Factors Affecting Back Pain among Patients after Cardiac Catheterization - Masoumeh Neishabory; Tahereh Ashke-; Hamid Alavi-Majd (Iran University of Medical Sciences, 2010)
Background and Aim: Cardiac catheterization is a widely used cardiac investigation procedure in Iran. However, back pain is frequently reported following cardiac catheterization due to prolonged bed rest after the procedure. There is no research about factors that affect back pain. This study was designed to explore these factors in patients admitted to Taleghani hospital for cardiac catheterization in 2006-2007.   Material and Method : This descriptive study was conducted on the 130 patients hospitalized for coronary angiography. Following a review of literature, gender, age, history of back pain, smoking, duration of the procedure, body mass index and chang positions were identified as potential factors affecting back pain level. Back pain was assessed at 6 hours and the morning after cardia catheterization. Questionnaire and numeric pain intensity scale were used for data collection.   Results: age (P<0.001) , gender (P<0.001) , history of back pain (P<0.001) , body mass index (P<0.001) and chang position (P<0.001) were significantly related to the level of back pain after angiography.   Conclusion : The results may help nurses to have a better understanding about patients' physical needs and appropriate nursing interventions that can be planned to enhance patient comfort following cardiac catheterization.